Peningkatan Angka Kebuntingan melalui Pemberian Hormone Eksogen CIDR-B dan Injeksi hCG pada Sapi Bali di Kecamatan Pemayung Kabupaten Batang Hari - Depison, Depison (Fakultas Peternakan Universitas Jambi, 2009)
This eksperiment was conducted in order to know 1) The effect of hormone CIDR-B and the injection of hCG on increased conception rates in post-IB Bali cattle in Sub District Pemayung Batang Hari. 2) Application and dissemination technology of the use of exogenous hormone in improving the reproductive performance of Bali cattle, especially in villages in the subdistrict Pemayung Batang Hari. The method used to reveal the data was an experiment by using 90 Bali cattle in several villages in the District Pemayung. The treatments used were R1 (control) without treatment, R2, Hormones CIDR-B, R3 hCG injection. The average value of non-return rate (NR) results of these activities was 68.89%. The use of CIDR-B was implanted day 7 to day 14 after IB and hCG day 7 post-IB in sequence to increase the number of animals who did not return estrus compared with no hormonal treatment by 20% and 16.66%. The average parent who declared pregnant Bali cattle after pregnancy examination (PKB) at 2 months of gestation was 60%. Based on the results and the discussion can be concluded that the provision of exogenous hormones CIDR-B and hCG can increase gestation Bali cattle in terms of NR and CR and the best was the use of hormone CIDR-B.